Textbook Knowledge: Fact or Fiction. - Copeland, Ronald M.; Mead, George C. (The Accounting Review, 1969)
The article discusses the practical implications of accounting knowledge. Accounting is not a static field; on the contrary, it is continually evolving in reflection of underlying changes in the dynamic economy. Yet accounting textbooks too often are reluctant to introduce change once a subject becomes part of the "accepted body of knowledge." Much of the information contained in current accounting textbooks bears no relationship to current accounting – thought or practice. Advanced textbooks all introduce bankruptcy procedures by way of a discussion of a Statement of Affairs, which purportedly is used to disclose the financial condition of an insolvent business. Practitioners should make some effort to audit theft academic brethren. All new textbooks should be reviewed by one competent to appraise the validity of the text material. Clear misstatements of fact should be brought to the attention of the author. In this regard, authors must make a more complete effort to insure the authenticity or relevance of the material CPA Examination question and described in most texts misrepresents fact.